Do Microcredit Loans Do What They Are Intended To Do? A Case Study of the Credit Village Microcredit Programme in China. (24th April 2020) - Jiang, Meishan; Paudel, Krishna P.; Zou, Fan
Abstract: The purpose of this study is to assess if the credit village is an effective way to develop a microcredit programme in China from the perspective of poverty reduction policy and risk monitoring. Cross‐sectional household survey data from three credit villages in the Yunan County of China are analysed using 3SLS and IV probit models. The major finding is that the credit village loosens credit restrictions to some extent. However, it has no impact on educational expenditures, medical expenditures, long‐term assets, short‐term assets and women's rights. It is our observation that the microcredit programme in China needs more innovation to become effective. © 2020 John Wiley & Sons, Ltd.